The Use of Snowball Throwing Learning Model in Improving the Writing Ability - Fatmawati Fatmawati (Universitas Sulawesi Barat, 2018)
This research is aimed at finding out: the use of snowball throwing learning model significant develop the students’ writing ability of the tennth year students of SMA Negeri 1 Halteng. Related to the aim of the research, a quasi-experimental design was carry out. The population was the tenth year students of SMA Negeri 1 Halteng. Two classes chose randomly as sample. As the result, the experimental group consisted of 30 students while the control group consisted of 30 students. The data was collected through writing test which was conducted through two terms namely pretest and posttest. The data required from writing test was analyzed by using t-test and percentage technique. The result of this research indicated that The use of Snowball Throwing Learning Model was able to improve the students’ writing ability. The result of the research indicated that there was significant different of the students’ achievement on writing ability of students who were taught by Snowball Throwing Learning Model and by conventional way (direct instruction technique). It is proved by t-test value of students posttest (3.73) which greater than pretest (0.06). the t-test (3.73) was greater than t-table value (2.021) for 0,05 level of significance, degree of freedom (N1+N2 - 2)= 58.